59.4k views
2 votes
U = vw + z, solve for v

User Decyclone
by
5.0k points

1 Answer

3 votes

ANSWER


\text{ v = }\frac{u\text{ - z}}{w}\text{ or }(u)/(w)\text{ - }(z)/(w)

Step-by-step explanation

We are given that:

u = vw + z

We want to solve for v.

First, take z to the left hand side:

u - z = vw

Now, divide through by w:


\begin{gathered} \frac{u\text{ - z}}{w}\text{ = v} \\ \Rightarrow\text{ v = }\frac{u\text{ - z}}{w}\text{ or }(u)/(w)\text{ - }(z)/(w) \end{gathered}

That is the answer.

User Vlad Rudenko
by
4.7k points